The SCARE 2018 statement: Updating consensus Surgical CAse REport (SCARE) guidelines. (December 2018) - ,; Zhu, Hongyi; Alsawadi, Abdulrahman; Noureldin, Ashraf; Rao, Ashwini; Enam, Ather; Thoma, Achilleas; Bashashati, Mohammad; Vasudevan, Baskaran; Beamish, Andrew; Challacombe, Ben; De Wilde, Rudy Leon; et al.
Abstract: Introduction: The SCARE Guidelines were published in 2016 to provide a structure for reporting surgical case reports. Since their publication, SCARE guidelines have been widely endorsed by authors, journal editors, and reviewers, and have helped to improve reporting transparency of case reports across a range of surgical specialties. In order to encourage further progress in reporting quality, the SCARE guidelines must themselves be kept up to date. We completed a Delphi consensus exercise to update the SCARE guidelines. Methods: A Delphi consensus exercise was undertaken. All members of the previous Delphi group were invited to participate, in addition to researchers who have previously studied case reports, and editors from the International Journal of Surgery Case Reports. The expert group was sent an online questionnaire where they were asked to rate their agreement with proposed changes to each of the 24 items. Results: 56 people agreed to participate and 45 (80%) invitees completed the survey which put forward modifications to the original guideline. The collated responses resulted in modifications. There was high agreement amongst the expert group. Conclusion: A modified and improved SCARE checklist is presented, after a Delphi consensus exercise was completed. The SCARE 2018 Statement: Updating ConsensusS urgicalCA seRE port (SCARE) Guidelines. Highlights: A Delphi consensus exercise to update the SCARE guidelines. 45 (80%) invitees completed the survey and there was high agreement amongst the expert group. The collated responses resulted in modifications, and a improved SCARE checklist is presented.